Generalized Anxiety Disorder (GAD): A Literature Review - Putra, Anak Agung Gede Agung Difa Agusta Pramana; Dwiputri, Adelya Rahma; Madani, Ayda Fitri; Ramadhani, Dhea Asty; Maolidi, Juan; Rabbani, Muhammad Afif; Rizky, Muhammad Ilham; Adni, Azizatul (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Generalized anxiety disorder (GAD) is a psychological disorder characterized by persistent and uncontrollable feelings of anxiety and worry that last for at least 6 months. In 2019, there were 301 million people in the world experiencing anxiety disorders, making GAD the most common mental disorder in the world. This literature review aims to increase knowledge about generalized anxiety disorder so that it can increase treatment rates and decrease social stigma attached to GAD. Sources for this review were gathered through online databases including review articles, research studies, and professional guidebooks related to the topic. The review results show that GAD has a wide range of risk factors including personal, social, and environmental factors. GAD can have severe complications if not treated properly, hence highlighting the need for early detection and effective treatments.